A typology of small business growth modelling: A critical literature review - Krzysztof Wach (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to explore how corporate growth in business studies is explained and to present the typology of growth models of small businesses. Research Design & Methods: This conceptual article relies on literature review and desk research. The article elaborates on available literature via a critical literature review methodology. Findings: A detailed literature query, conducted for the purposes of this article, identified eight approaches to modelling corporate growth (growth of small businesses). Those are stochastic approach, stages models, evolutionary approach, resource-based view, learning approach, managerial approach, econophysical approach, and sustainable models. Implications & Recommendations: The literature query and the process of logical reasoning based on the collected material allows to outline several directions of further research. Firstly, future studies should conduct a detailed bibliometric analysis with a map of connections that will allow a classification of research areas. Secondly, scholars should prepare a more integrated approach towards the growth of small businesses, which will include more factors rooted in the entrepreneurship theory. Contribution & Value Added: The article structures scientific knowledge on the typology of modelling corporate growth in business studies. This article paid special attention to modelling of corporate growth of small and medium-sized enterprises, which in the case of firms of this size class run differently than in the case of large companies and international corporations, for which various models are mainly created.
Keywords: L25; L26; 330; entrepreneurship; corporate growth; growth modelling; growth management; small business; small and medium-sized enterprises